Review of Sharia Economic Law Concerning Consumer Protection in the Sale and Purchase of Used Vehicle Parts: at the Notoharjo Market, Surakarta City - Afief El Ashfahany; Yogi Dwi Saputra; Yayuli Yayuli (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2023)
The purpose of this study is to find out the practice of buying and selling used auto parts, to find out consumer protection in the practice of buying and selling used auto parts, to find out the review of Islamic law in the practice of buying and selling used auto parts at Kliwon Market, Surakarta. The method used is a descriptive method with a qualitative research type. The type of data used in this research is primary and secondary data. The data collection techniques used are observation, interviews, documentation. Data analysis using qualitative analysis. The results of the research show that the practice of buying and selling in the Klithikan market is identified as gharar qalil. This gharar is still understandable and does not reach buying and selling which is prohibited by sharia.